European and German electricity prices in times of natural gas crisis - Mathias Mier (EconPol Forum, 2022)
Nuclear stretching operation in Germany until April 15, 2023 brings down German (European) power prices by 6.01 percent (1.51 percent) until April 15, 2023 and by 2.98 percent (0.65 percent) in 2023, saving 4.8 TWH (8.6 TWh) of natural gas and 3.3 Mt (4.5 Mt) of CO2 emissions in 2023. Nuclear extension in Germany until 2029 would bring down German (European) power prices by 7.31 percent (1.79 percent) in 2023 and 2.95 percent (0.92 percent) in 2024, saving around 6.6 TWh (12.9 TWh) of natural gas and 13.3 Mt (17.8 Mt) of CO2 emissions in 2023. Reduced 2022 hydropower generation and reduced 2022 French nuclear availability contributes 2.21 percent (32.3 percent) to 2022 German (European) electricity price increases. Windfall tax is preferred to the revenue cap for "inframarginal" generators suggested by the European Commission
Keywords: 330